2022
DOI: 10.3390/ijerph191911956
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Overt and Relational Bullying on Adolescents’ Subjective Well-Being: The Mediating Mechanisms of Social Capital and Psychological Capital

Abstract: Based on the social and psychological capital framework, this study aimed to investigate the direct effect of bullying on adolescents’ subjective well-being and to reveal the potential psychosocial mechanisms in this relationship. Through the multi-stage cluster random sampling procedure, a cross-sectional survey was conducted among 728 adolescents from Hebei Province in China. Structural equation modeling was adopted for data analysis. After controlling for sociodemographic variables, the results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Still, results showed that physical and verbal victimization seemed to have a stronger association with low levels of adolescents' meaning in life than relational victimization. Being physically and verbally bullied may aggravate the feeling of unsafety and jeopardize self‐worth, leading to uncertainty about the values of one's own life (Hu et al, 2022). Compared to relational victimization, which concentrates on one's social relations with the surroundings (Olweus & Breivik, 2014), physical and verbal victimization is deemed more overt and tends to threaten adolescents' perceptions and beliefs towards themselves and their lives more directly, including their perceptions of life meanings (Siyahhan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Still, results showed that physical and verbal victimization seemed to have a stronger association with low levels of adolescents' meaning in life than relational victimization. Being physically and verbally bullied may aggravate the feeling of unsafety and jeopardize self‐worth, leading to uncertainty about the values of one's own life (Hu et al, 2022). Compared to relational victimization, which concentrates on one's social relations with the surroundings (Olweus & Breivik, 2014), physical and verbal victimization is deemed more overt and tends to threaten adolescents' perceptions and beliefs towards themselves and their lives more directly, including their perceptions of life meanings (Siyahhan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, relational victimization is hidden in most of the cases. The emotional and psychological damage and abuse may be more traumatic to female college students’ development and lead to more stress and negative emotional experience [ 78 ]. In the context of the current COVID-19 pandemic, the importance of interpersonal relationships has become more prominent, but the pandemic has hindered face-to-face interpersonal interaction and brought more negative experiences [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Positive psychological capital plays a crucial role in enhancing subjective well-being, alleviating negative emotions, coping with workplace bullying, and adapting to the environment [25][26][27][28][29]. Te impact of psychological capital can be observed through direct efects, indirect efects, moderating efects, and mediating efects.…”
Section: Te Relationship Between Perceived Social Support Positive Ps...mentioning
confidence: 99%